KEMAJUAN PENELITIAN DAN PUBLIKASI TENTANG KONSELING MULTIKULTURAL : TINJAUAN DAN ANALISIS BIBLIOMETRIC - Harahap, Jumli Sabrial; Silvianetri, Silvianetri; Hayati, Rida (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2024)
Abstract: Multicultural counseling, also called cross-cultural counseling, is a form of counseling that aims to understand clients with diverse backgrounds and characteristics. This study aims to see and analyze the development of scientific papers published in Scopus on multicultural counseling. The research method uses a literature review, especially using bibliometrics. Data retrieval was obtained from the Scopus web using the keyword